Antiphospholipid syndrome: state of the art on clinical practice guidelines. (18th October 2018) - Limper, Marteen; Scirè, Carlo Alberto; Talarico, Rosaria; Amoura, Zahir; Avcin, Tadej; Basile, Martina; Burmester, Gerd; Carli, Linda; Cervera, Ricard; Costedoat-Chalumeau, Nathalie; Doria, Andrea; Dörner, Thomas; et al.
Abstract : Antiphospholipid syndrome (APS) is a rare disease characterised by venous and/or arterial thrombosis, pregnancy complications and the presence of specific autoantibodies called antiphospholipid antibodies. This review aims to identify existing clinical practice guidelines (CPG) as part of the ERN ReCONNET project, aimed at evaluating existing CPGs or recommendations in rare and complex diseases. Seventeen papers providing important data were identified; however, the literature search highlighted the scarceness of reliable clinical data to develop CPGs. With no formal clinical guidelines in place, diagnosis and treatment of APS is largely based on consensus and expert opinion. Patients' unmet need refers to the understanding of the disease and its clinical picture and implications, the need of education for patients, family members and healthcare providers, as well as to the development of monitoring pathways involving multiple healthcare providers.